Penelusuran Waduk Mrica untuk Analisis Perubahan unjuk Kerja Fungsi dan Efisiensi Penggelontoran Sedimen : Mrica Reservoir Routing for The Analysis of Change In Functional Performance and Sediment Flushing Efficiency - Rahadiansyah, Shakti; Ariyanti, Vicky; Sulaiman, Muhamad; Kurniawan, Adhy; Legono, Djoko (Himpunan Ahli Teknik Hidraulik Indonesia (HATHI), 2025)
Mrica Reservoir, also known as the Panglima Besar Soedirman Dam, was constructed in 1982 and serves multiple purposes, including electricity generation, irrigation, and flood control. The main problem faced over the past decade is the very active sedimentation of the reservoir, which is felt to have caused a decline in the reservoir's function as originally planned. This paper presents the results of evaluating the efficiency of sediment removal from Mrica Reservoir by flushing. The RESROUT2 (Reservoir Routing Version 2) was developed to study the water (and sediment) balances and to evaluate the influence of changes in the characteristics of the Mrica Reservoir (with a specific reservoir inflow characteristic) on the outflow pattern. Reservoir outflow is made possible by regulating the output facilities, such as spillways, intake structures for power and irrigation, power generation, and a drawdown culvert to release sediment. The volume of flow out through the bottom outlet and the flushing efficiency for 5 hours are 4.354 million m3 and 0.167, respectively, while for 3 hours of flushing, they are 2.476 million m3 and 0.221, respectively. Increasing the efficiency of sediment flushing in the Mrica Reservoir still needs to be pursued along with efforts to reduce its negative impacts.